La interpretación en el derecho tributario - Chávez Gonzales, Ángel Marco (Universidad ESAN, 2021)
Tax controversies in part are originated by the different interpretations of the tax regulations between tax administration and taxpayers, so the issue of the interpretation of the tax regulations is of academic interest for this reason we have resorted to the doctrine and from a practical point of view to the resolutions of the Tax Court and the judgments of the Supreme Court. This article begins showing what tax controversies mean in numbers; then referring to the a priori approach of the interpreter, known as general interpretation criteria; also we will discuss the methods of interpretation; after we will see the apothegms of interpretation, which are topical arguments of fairly general acceptance; finalizing the article with the analogy, the excessive interpretation of the rule and the interpretation of the tax relief.

Las controversias fiscales impugnadas se originan en parte en las distintas interpretaciones de las normas tributarias que aplican la Administración Fiscal y los contribuyentes, de ahí que este tema sea de interés académico. Para abordarlo, se ha recurrido a la doctrina y, desde un punto de vista práctico, a las resoluciones del Tribunal Fiscal y a las sentencias de casación del Poder Judicial. Este artículo comienza mostrando lo que significan en números las controversias tributarias; luego trata la interpretación de la norma tributaria, con referencia a la aproximación apriorística del intérprete, que es lo que se conoce como criterios generales de interpretación. A continuación, el artículo se ocupa de los métodos de interpretación; seguidamente se verán los apotegmas de interpretación, que son argumentos jurídicos aceptados a los cuales el intérprete recurre. El artículo finaliza con la analogía, la interpretación excesiva de la norma y la interpretación de la desgravación tributaria.
Keywords: Interpretation of tax rules; Interpretive criteria; Interpretación de las normas tributarias; Methods of interpretation; Criterios interpretativos; Interpretation apothegms; Métodos de interpretación; Apotegmas de interpretación; Analogy; Analogía; https://purl.org/pe-repo/ocde/ford#5.05.01